EFFECT OF BUDGET PARTICIPATION, ORGANIZATIONAL COMMITMENT, WORK SATISFACTION, JOB RELEVANT INFORMATION, ORGANIZATIONAL CULTURE AND LOCUS OF CONTROL ON PERFORMANCE OF EMPLOYEES FINANCIAL PART OF EDUCATION DIVISION REGENCY OF KLATEN - Joko Sutopo (ADVANCE, 2018)
The purpose of this study is to analyze and provide empirical evidence of significant influence of Budget Participation, Organizational Commitment, Job Satisfaction, Organizational Culture, Job Relevant Information and Locus Of Control on the Performance of Personnel of Finance Division at Klaten District Education Office. The population in this study is the financial officer of Education Department of Klaten Regency that meets the criteria, so that the sample that meets the criteria and can be studied as much as 34 employee of finance department to be the repondent. The method of analysis in this study consisted of, instrument testing, classical assumption test, multiple linear regression analysis, t test, and R2 test. Instrument test results show that the instrument statement is valid and reliable. Instrument test results show that the instrument statement is valid and reliable. The results of the classical assumption test show that all variables have a normal distribution, free from multicollinearity, does not contain any heterokedastisitas and there is no autocorrelation. The results of the classical assumption test show that all variables have a normal distribution, free from multicollinearity, does not contain any heterokedastisitas and there is no autocorrelation. The result of hypothesis testing shows that Budget Participation has positive and not significant effect on Employee Performance of Finance Department, Organizational Commitment have positive and insignificant effect on Employee Performance of Finance Division, Job Satisfaction has negative and insignificant effect on Employee Performance of Finance Department, Job Relevant Information has negative effect and not significant to Employee Performance Finance Section, Organizational Culture have a positive and insignificant effect on Employee Performance Finance Section, Locus Of Control have positive and significant effect to Performance of Finance Officer. The result of R2 test (coefficient of determination) is known that Budget Participation, Organizational Commitment, Job Satisfaction, Job Relevant Information, Organizational Culture, and Locus Of Control are able to explain 38,3% to Employee Performance variable of Finance Department, while the rest equal to 61,7% explained by other variables such as motivation, work discipline, and work environment. Keywords: Employee Performance Finance Section, Budget Participation, Organizational Commitment, Job Satisfaction, Job Relevant Information, Organizational Culture, and Locus Of Control